(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In the past, humans had to rely more on natural resources. They relied so heavily on plantsfor food and medicine that they tapped into the commercial and medicinal possibilities of many differentkinds of plants. The earliest references to the use of plants for medicinal reasons in Hindu culture maybe found in the Rig Veda, often regarded as the oldest reservoir of human knowledge. Many studieson India’s unique flora have been published by ethnobotanists from different parts of the nation.However, this is why Chhatarpur is so understudied. Therefore, the present study has included manyfield surveys in various locations throughout the state of Chhatarpur, 2020–2021, to examine and recordethnobotanical data.